Megtakarítási típusok: Egy adaptív-evolúciós megközelítés - János Vincze; Gergely Varga (Hungarian Academy of Sciences, Institute of Economics, 2015)
– Macroeconomic modelling is a recent development within the rapidly advancing field of agentbased modelling. Like older macromodels macro ABMs must also feature a well-designed consumption-savings block. As the microeconomic ABM literature on savings is non-existent researchers had to resort to the traditional literature to borrow ideas about how to model agents' savings behaviour. They adopted certain simple consumption rules as simplifications of the (implicit) decision rules derived from maximizing models. In this paper we set up an agentbased macromodel where households belong to one of three types of savers (prudent, myopic, permanent income based), but allow for adaptation, learning and selection. We are interested in establishing the relative fitness of the three savings types, and determine their impact on the overall performance of the economy. Through running simulations we find that the prudent type alone prevails when the selection pressure is very high, but at intermediate levels of evolutionary competition the two other types can survive as well. At customary levels of relative capital efficiency prudent agents tend to overaccumulate capital, and the presence of the other types is like a socially useful antidote, driving the long-run savings rate towards the golden rule. On the other hand low selection pressure raises substantially the volatility of capital. In this model relaxing borrowing constraints is conducive to even more excessive investments, as if owners of capital were exploited by wage-earners.
Keywords: E03; E14; E27; 330; savings types; bounded rationality; evolutionary learning; agent-based macromodel